Pengaruh Kinesio Taping Terhadap Kekuatan Otot Dorsal Flexor Ankle Pada Pasien Kusta Dengan Lesi Nerve Peroneus di Unit Rehabilitasi Kusta RSUD Kelet Provinsi Jawa Tengah - Roy, Adryan, Umi Budi Rahayu, S.Fis, M.Kes (2017)
Background: Leprosy is a chronic infectious disease caused by Mycobacterium leprae attacking peripheral nerves and other body organs except central nerves system. If the nerve damage reaches nerve peroneus, then it causes weakness/paralysis of dorsal flexor ankle muscle. One of physiotherapeutic roles is to prevent a physical defect to be worst. Solution offered is a fixing of kinesio taping in order to improve muscle strength. Purpose: Purpose of the research is to know effect of kinesio taping on strength of dorsal flexor ankle muscle of leprosy patient with nerve peroneus lesion. Method: This research is quantitative study with quasi-experimental method with pre and post with control group design. Results: Data was normally distributed and homogenous variance. Hypothesis testing using Paired Sample T-Test for treatment group (p=0,031< α = 0,05) means there is an effect of kinesio taping; in the other hand in control group (p = 0,051 > α = 0,05) means there is no effect. Independent Sample T-test obtained p value (p = 1.190 > α=0.05) meaning that Ho is accepted. It showed that there is no difference effect between kinesio taping and control group on strength of dorsal flexor ankle muscle of leprosy patient with nerve peroneus lesion was not found. Conclusion: Practically, kinesio taping has effect on strength of dorsal flexor ankle muscle of leprosy patient with nerve peroneus lesion. However, statistically the effect of kinesio taping had been not found on strength of dorsal flexor ankle muscle (p=0.190)